Solvent-mediated molar conductivity of protic ionic liquids - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Physical Chemistry Chemical Physics, 2015)
The molar conductivity, A(m), of protic ionic liquids (PILs) in molecular solvents is measured at 298.15 K. The decrease in the A(m) values of PILs is observed with an increase in the concentration of PILs. The limiting molar conductivities, A(m)(0), were obtained for each PIL in different molecular solvents using a least squares method. The A(m)(0) data for PILs were correlated with the structural aspects of PILs and solvent properties. The polar protic solvents show poor ionic association as compared to the polar aprotic solvents, which is discussed on the basis of the hydrogen bond donating (HBD) ability of solvents and PILs. The alkyl chain substitution of anions plays a significant role in the ionic association of the PILs. The diffusion coefficient D-0 and the transport number t were determined, which were consistent with the A(m)(0) values of PILs in water. The A(m)(0) and D-0 values are dependent on the hydrodynamic radius of anions of these ionic liquids. The extent of ionic association for each PIL was discussed using temperature dependent A(m) data for aqueous PIL systems in terms of the Walden plot.